Improving the Mathematics Learning Outcomes on Measurement Material Through Measurement Card Media in 3rd Grade Students at SD 1 Al-Islam Surakarta - Ni’matul Choirunnisa; Nifa Anggita; Oryza Riana Anggraini; Puspita Indra Wardhani; Jamaluddin (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Mathematics learning is still considered difficult for some students due to the abundance of numerical information, which affects students' learning outcomes. This study aims to improve the mathematics learning outcomes of third-grade students at SD 1 Al-Islam Surakarta on the topic of measurement using measurement cards as a learning medium. This research uses the Classroom Action Research (CAR) method with a quantitative approach. Data analysis techniques utilize descriptive statistical methods in the form of percentages. Data collection techniques include observations, interviews, and cognitive tests. The results show that students' learning completeness improved in each cycle. In the pre-cycle, the completion percentage reached 48%. After the application of the measurement card medium in Cycle I, the learning completeness increased to 68%, and in Cycle II, there was a significant improvement of 12%, reaching a learning completeness of 80%, with an average score of 85.6. Therefore, it can be concluded that the use of measurement cards can enhance students' learning outcomes in the mathematics measurement topic.